Financial Services: Perspectives and Challenges. - Eisenbeis, Robert A.; Hayes, Samuel L. (Journal of Finance, 1995)
Nine papers commissioned by Harvard Business School faculty for a colloquium in May 1992 delve into a variety of issues and developments faced by managers of financial intermediaries in the rapidly changing banking industry. They include deregulation, the thrift crisis, international insurance, and